Co-encapsulation of thymoquinone with docetaxel enhances the encapsulation efficiency into PEGylated liposomes and the chemosensitivity of MCF7 breast cancer cells to docetaxel. Issue 11 (November 2019) - Odeh, Fadwa; Naffa, Randa; Azzam, Hanan; Mahmoud, Ismail S.; Alshaer, Walhan; Al Bawab, Abeer; Ismail, Said
Abstract: Combinatorial therapeutic strategies to eradicate tumors can be superior to a single therapeutic modality. Docetaxel (DT) has been approved for the treatment of local or metastasized breast cancer alone or in combination with other chemotherapeutic agents. Thymoquinone (TQ) originated from the seeds of Nigella Sativa plant has been reported to possess in vitro and in vivo antitumor activity against variety of tumors. In the current study, we have investigated the synergistic anticancer efficacy of a novel combination of DT and TQ on MCF7 breast cancer cell line using MTT cell viability assay. Moreover, this study describes for the first time the co-encapsulation of DT and TQ into PEGylated liposomes. The results showed that the combination of DT and TQ resulted in significant synergistic cytotoxicity compared to DT and TQ alone. Moreover, DT and TQ have been successfully co-encapsulated into PEGylated liposomes with higher encapsulation efficiency compared to DT and TQ alone. In conclusion, DT and TQ combination poses a synergistic effect and may aid in decreasing the required doses of DT. Also, the co-encapsulation of DT and TQ into PEGylated liposomes can provide a promising DT and TQ delivery system into cancer cells. Abstract : Cancer research; Pharmaceutical science; Breast cancer; Docetaxel; Thymoquinone; Liposomes; Delivery system; Combination therapy